2018
DOI: 10.1002/cphc.201800102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnesium Bond on the Competition Between Hydrogen and Halogen Bonds and the Induction of Proton and Halogen Transfer

Abstract: HOX (X=Cl, Br, I, and At) can engage in either a H-bond (HB) or halogen bond (XB) with a base-like HCN, NH , and imidazole. Although the former is energetically preferred for X=Cl and Br, it is the XB that is more stable for At, with I showing little preference. MgY forms a Mg-bond with the O atom of HOX, which grows stronger in the order X=Cl Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 78 publications
(127 reference statements)
0
17
0
Order By: Relevance
“…[29,30] By combining interactions that do not compete for the same binding sites, it is, in principle, possible to avoid or at least minimize ''synthon cross-over'', [31] thereby producing architectures of considerable complexity. [34][35][36][37][38][39][40][41][42][43] This is not only because HBs and XBs are similar in strength and properties, but also they are widely applicable to biochemistry and drug design. [33] There are many studies on the competition between various interactions, especially the competition between hydrogen and halogen bonds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[29,30] By combining interactions that do not compete for the same binding sites, it is, in principle, possible to avoid or at least minimize ''synthon cross-over'', [31] thereby producing architectures of considerable complexity. [34][35][36][37][38][39][40][41][42][43] This is not only because HBs and XBs are similar in strength and properties, but also they are widely applicable to biochemistry and drug design. [33] There are many studies on the competition between various interactions, especially the competition between hydrogen and halogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the well documented issue of the nature of the Lewis acid and base, [44] there are other important factors such as solvent polarity. [46][47][48][49][50][51][52][53][54][55][56] In a recent work, Xu et al observed the effect of a magnesium bond (Mg-bond) on the competition between HB and XB [38] and found that the Mg-bond enhances both the HB and XB, but the degree of this strengthening is different for the two. [46][47][48][49][50][51][52][53][54][55][56] In a recent work, Xu et al observed the effect of a magnesium bond (Mg-bond) on the competition between HB and XB [38] and found that the Mg-bond enhances both the HB and XB, but the degree of this strengthening is different for the two.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooperativity also affects the competition between HB and XB. For example, the presence of magnesium bonding has a positive synergistic effect on the strength of HB and XB, but the enhancing effect on both interactions is different . Of course, whether it is HB or XB, its strength depends mainly on the properties of Lewis acid and Lewis base.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the presence of magnesium bonding has a positive synergistic effect on the strength of HB and XB, but the enhancing effect on both interactions is different. [38] Of course, whether it is HB or XB, its strength depends mainly on the properties of Lewis acid and Lewis base. Therefore, many studies have been conducted on the effects of Lewis acid and Lewis base on the competition between HB and XB.…”
Section: Introductionmentioning
confidence: 99%